2003
DOI: 10.1292/jvms.65.549
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of Porcine Pancreatic Endocrine Cells to Total Pancreatectomized Dogs

Abstract: ABSTRACT. Xenotransplantation of porcine pancreatic endocrine (PE) cells in a diffusion chamber, a bioartificial endocrine pancreas (Bio-AEP), was conducted to total pancreatectomized dogs. Six pancreatectomized dogs were divided into two groups of 3 dogs each. In three dogs of the control group, exogenous insulin was administered twice a day for 30 weeks to maintain fasting blood glucose (FBG) levels within the normal range. The remaining three dogs were implanted with Bio-AEPs (implantation group), in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Recipients: Five Beagle dogs that had been transplanted with approximately 1.0 to 2.0 × 10 8 porcine PE-cells were used [4]. Porcine PE-cells were embedded in the diffusion chamber type Bio-AEP constructed of a silicon ring and two nucleopore membranes with a pore size of 0.1 µm [4,10].…”
Section: Detection Of Perv Messenger Ribonucleic Acid (Mrna) From Thementioning
confidence: 99%
See 2 more Smart Citations
“…Recipients: Five Beagle dogs that had been transplanted with approximately 1.0 to 2.0 × 10 8 porcine PE-cells were used [4]. Porcine PE-cells were embedded in the diffusion chamber type Bio-AEP constructed of a silicon ring and two nucleopore membranes with a pore size of 0.1 µm [4,10].…”
Section: Detection Of Perv Messenger Ribonucleic Acid (Mrna) From Thementioning
confidence: 99%
“…Porcine PE-cells were embedded in the diffusion chamber type Bio-AEP constructed of a silicon ring and two nucleopore membranes with a pore size of 0.1 µm [4,10]. Bio-AEP was implanted into the abdominal cavity of the dog without fixation.…”
Section: Detection Of Perv Messenger Ribonucleic Acid (Mrna) From Thementioning
confidence: 99%
See 1 more Smart Citation
“…Kin et al demonstrated insulin independence for 6–119 days in pancreatectomized dogs receiving xenogeneic porcine islets encapsulated in agarose and polystyrene sulfonic acid [10]. A bioartificial endocrine pancreas consisting of porcine islets contained in an agarose matrix within semipermeable membranes was also shown to reduce insulin requirements in pancreatectomized dogs for up to 17 weeks [11]. …”
Section: Introductionmentioning
confidence: 99%
“…65,69 Extravascular devices refer to macroencapsulated cells that are implanted outside of the vasculature, e.g., subcutaneously, intraperitoneally, or in the omentum. Although these devices, such as hollow fibers, diffusion chambers, and polymeric sheets, yielded encouraging results in rodents [70][71][72][73][74][75][76][77] and canines, [78][79][80] their large size and exclusive reliance on diffusive transport resulted in islet dysfunction and device failure in the long term. Mathematical modeling predicts inadequate transport profiles, indicating scalability of these devices to larger animal models will be problematic after islet density optimization, thereby rendering such implants bulky or requiring multiple devices.…”
Section: Macroscale Encapsulationmentioning
confidence: 99%